Self-management training vs. neurofeedback interventions for attention deficit hyperactivity disorder: Results of a randomized controlled treatment study - Korfmacher, Ann-Kathrin; Hirsch, Oliver; Chavanon, Mira-Lynn; Albrecht, Björn; Christiansen, Hanna (Frontiers in Psychiatry, 2022)
Objectives: Neurofeedback (NF) and self-management training (SMT) may be viable treatment options for patients with Attention Deficit Hyperactivity Disorder (ADHD) if they alleviate core symptoms, enhance the patients’ self-concept and improve their quality of life. Aim of the current study is evaluating both interventions accordingly and to test whether specific improvements in core symptoms lead to more general improvements in self-concept and quality of life. Methods: In a psychotherapeutic outpatient clinic in Germany, a total of N = 139 children with ADHD were screened for eligibility, of which 111 fulfilled inclusion criteria and participated in the study in accordance with the CONSORT 2010 statement. These were randomly assigned to NF vs. SMT interventions. Changes from pre- to post-intervention in core ADHD symptoms relying on parent and teacher reports (CONNERS 3) and objective tests (QbTest) as well as self-concept (interview with the children) and quality of life assessments (using the KINDL-R self-report) were compared between patients receiving NF or SMT. Results: Significant improvements in ADHD symptoms were achieved similarly in both treatment groups, whilst quality of life and self-concept improved after SMT only. Conclusion: This treatment study provides further evidence that SMT and NF may reduce core symptoms, but SMT may also improve patients’ self-concept and quality of life and may thus in its current form be the favorable treatment option in naturalistic settings. However, several limitations of the current study implicate that further research is required before definitive conclusions and recommendations for clinical practice can be given.